A system for the acquisition and analysis of the 3D mandibular movement to be used in dental medicineDocumento electrónico - Isa C. T. Santos (2007)
The peculiar construction of the temporomandibular joint allows the mandible to move accord-ing to six degrees of freedom. In Dental Medicine, is essential to know this movement to simulate the tem-poromandibular joints, to position tooth moulds in articulators and to reproduce the mandibular movements in order to insure a satisfactory occlusion. In this work a facial arc, commonly used in Dental Medicine, was adapted to use electromagnetic sensors with the purpose of acquire the 3D mandibular movement. Some parts of the chosen facial arc were redesigned, and it was developed a specific support for the sensors employed. To visualise and analyse the acquired movement it was developed a software application using LabVIEW.